A case of myeloid sarcoma masquerading as neuroblastoma - Hassan, Siti Amirah; Sivaratnam, Dhashani; Devaraj, Navin Kumar; Teh, Kok Hoi; Abdul Razak, Rosniza; Ching, Siew Mooi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Myeloid sarcoma (MS) is an uncommon type of malignancy, and its diagnosis is comparable to acute myeloid leukaemia (AML). In the rare circumstances in which MS does present without AML, it is known as MS de novo. We report a case of a 10-month old child who presented with bilateral proptosis and a pelvic mass due to synchronous primary MS de novo. She was initially misdiagnosed with neuroblastoma, which has this typical presentation. The histopathological result from the biopsy of the orbital mass also showed a small blue round cell tumour (SBRCT) as seen in cases of neuroblastoma. However, the diagnosis of MS was confirmed using immunohistochemistry (IHC) from the orbital biopsy specimen, which usually plays a major role in the diagnosis of orbital tumours and as a prognostic indicator. Our patient remains in clinical remission two years after antileukemic treatment, with no relapse or progression to AML.